Effect of equal channel angular pressing processing routes on corrosion resistance and hardness of heat treated A356 alloy - Gebril, Mohamed A.; M. Zaidi Omar,; Nk. Othman,; I.F. Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Equal channel angular pressing (ECAP) via routes A and Bc was used to process heat treated A356 alloy. The samples produced a range of microstructures in order to investigate the effect of straining on its corrosion behavior in 3.5 wt. % NaCl solution and hardness. The ECAP was conducted at room temperature in a mold with channel angle of 120°. The results show that brittle coarse silicon particles were effectively fragmented into smaller size in the Al-rich matrix after the processing. The hardness and corrosion resistance test showed improvement after T5 and T6 heat treatment, preferably to T6 due to wholly changed in silicon particles morphology than T5. The hardness increased with ECAP processing from 60.66 Hv to 1133.47, 124.91 Hv after three passes route Bc and four passes route A, respectively. The evaluation of corrosion resistance of the alloy showed improvement from 0.0424 to 0.00173, 0.00149 mmy-1 after three passes route Bc and four passes route A, respectively. In this research, both strength and corrosion resistance are improved by ECAP processing of A356 alloy using both routes.